PREISCHEMIC ADMINISTRATION OF CITICOLINE EXERTS BETTER NEUROPROTECTION AND RESTORES NEUROCHEMICAL AND MOTOR FUNCTIONS IN MCAO/R RATS. - B. PRAMILA; P. KALAIVANI; R. BARATHIDASAN; C. SARAVANA BABU (International Journal of Pharma and Bio Sciences, 2015)
In the present study, the efficacy of citicoline in alleviating the ischemia/reperfusion neuronal injury was investigated in male Sprague Dawley rats. Citicoline was administered before inducing ischemia, during ischemia and after reperfusion. Animals were scored for neurological deficits, assessed for anxiety, cognition and motor activity. Sodium potassium ATPase, Glutamate, ATP, NAD was determined and western blot analysis of TNF-α and IL-10 was performed. Histopathology of the brain was performed. Citicoline has recuperated neurological deficits in the rats treated with citicoline before ischemia. Sodium potassium ATPase, ATP, NAD was increased and glutamate level was decreased in the Pre-ischemic L-NAME group than the other treatment groups. In addition to this, expression of TNF-α was down regulated, IL-10 was upregulated, and percentage neuronal damage was greatly reduced in the preischemic citicoline group. Hence, Pre-ischemic administration of Citicoline exhibits better neuroprotection in middle cerebral artery occluded / reperfused rats.